Clinical Signs and Laboratory Markers Compete Favorably with Antigen Detection of Canine Parvovirus-2 in Dogs - Akanbi, Olatunde Babatunde; Fagbohun , Olusegun; Kolawole , Aderonke Rachael; Olaifa , Olanrewaju Samuel; Aliyu, Victor; Ekong, Pius Stephen; Daodu, Oluwafemi Babatunde; Olopade, James Olukayode; Taiwo, Victor Olusegun (Media Kedokteran Hewan, 2025)
Thirty dogs (< 1 year) which reported to the Veterinary Teaching Hospital, State Veterinary Hospital and City Veterinary clinic, Ibadan between October 2023 and February 2024 and had clinical signs of depression, vomiting, diarrhea, anorexia, and fever were tested for canine parvovirus-2 by rapid antigen test and confirmed by PCR. Clinical signs (CS) presumptively diagnosed and CPV positive antigen tested dogs were recruited. A 13.33% infectivity rate was recorded in 4-weekolds and 20% in adult dogs between 7 and 12 months of age contrary to belief of parvoviral enteritis in dogs above 6 weeks. A combination of clinical signs in 28 of 30 dogs, 93.3% (95% CI: 77.9-98.2%, p ≤ 0.9918), were positive for CPV-2, and laboratory markers (LM) including leukopenia seen in 90% of CPV infected and thrombocytopenia observed in 100% of CPV infected dogs (95% CI: 88.4 - 100.0%, p ≤ 1.000) were confirmed positive for CPE, against 100.0% antigen detection (95% CI: 88.4 - 100.0%, p ≤ 1.000) in CPV infected. Therefore, the Clinical Signs and Laboratory Markers (CSLM) method for diagnosing CPE competes favorably with rapid antigen detection of Canine Parvovirus-2. The CSLM method can be explored as an alternate diagnostic tool in resource limited environments.